THE DISTRIBUTION OF OPTIONAL AND OBLIGATORY PLURAL MORPHEMES: CROSS-LINGUISTIC STUDY OF UZBEK -LAR AND KOREAN - 들 - Abdiraximova Iqboloy O’ktam qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  study  compares  how  Uzbek  and  Korean  express  plurality  through  the suffixes -lar and - 들 . Although both languages are agglutinative and share a subject–object–verb word order, they apply plural marking in different ways. Using 400 noun phrases from the Sejong Corpus (Korean) and the Uzbek National Corpus, we examine how animacy, definiteness, the presence of numerals, and syntactic position influence the use of  these suffixes.  The  results  reveal  a  clear  contrast: Uzbek  -lar is largely optional  and  frequently  omitted  when  context  or  a  number  word  already  indicates plurality. In contrast, Korean - 들  is strongly restricted to human and animate referents, systematically avoided with explicit numerals or classifiers, and preferred in formal registers. These findings demonstrate that plural marking in both languages is driven by semantic and pragmatic conditions rather than strict grammatical rules. The study contributes to cross-linguistic research on nominal number, offers practical insights for Uzbek–Korean language teaching, and provides empirically grounded constraints for machine translation and natural language processing systems.